Effect of 12 Weeks of Core Stability Exercises on Functional Movement and Balance of Women Working in Hospitals - Maryam Golmoradi Marani; Mahdi Khalegi; Aezam Ahmadi; Seyyedeh Fatemeh Alavi (Biyumikānīk-i varzishī)
Objective: This study aims to assess the effect of 12 weeks of core stability exercises on functional movement and balance of women working in hospitals. Methods: Participants were 34 women aged 30-50 years working in Imam Khomeini Hospital in Tehran, Iran. They were randomly divided into two groups of exercise and control. The exercise group performed core stability exercises for 12 weeks. The functional movement was evaluated using the valid Function Movement Screen (FMS) method. The dynamic balance, power, agility, speed and flexibility of subjects were also measured using Y balance test, Sargent Jump Test, agility T-test, 20-meter running test, and seated bending forward test, respectively before and after exercise. Paired T-test was used to examine the difference between pre- and post-test scores of each group. Analysis of Covariance (ANCOVA) was used to determine the effect of intervention on the study variables. Results: Results of ANCOVA showed that 12 weeks of core stability exercises significantly improved functional movement performance, dynamic balance, power, agility, speed and flexibility in women. Conclusion: Core stability exercises can improve the performance of neuromuscular system leading to proper movement of spinal, pelvic and hip joints, proper muscle balance, enhanced proximal stability, functional strength and resulting in decreased injury.